PENGARUH KOMPENSASI, MOTIVASI DAN FLEKSIBIBILITAS TERHADAP KEPUASAN KERJA DRIVER GOJEK DI KOMUNITAS DRIVER GOJEK WTC SERPONG, TANGERANG SELATAN - Bernandu Grandian Hasiando Nainggolan, (2022)
This research is using quantittative study aimed to see whether there are influence of compensation, motivation, and work flexibility on job satisfaction. This study uses the saturated sample method that the all of gojek drivers in WTC Serpong gojek drivers community, South Tangerang as samples. Testing hypothesis in this study was used Multiple Linear Regression Analysis using IBM SPSS version 24 analysis tool with a significant level of 5% (0,05). The results of these test indicate that (1) There is significant influence of compensation on job satisfaction, (2) there is significant influence of motivation on job satisfaction, and (3) there is no significant influence of work flexibility on job satisfaction. (4) Compensation, Motivation, and Work Flexibility simultaneously effect on job satisfaction Keywords: Compensation, Motivation, Work Flexibility, Job Satisfaction.